Effect of electrode spacing on image flicker in fringe-field-switching liquid crystal display. Issue 7 (27th May 2016) - Oh, Seung-Won; Park, Jun-Hee; Baek, Jong-Min; Choi, Tae-Hoon; Yoon, Tae-Hoon
ABSTRACT: Low-frequency driving of a liquid crystal display (LCD) panel to minimise power consumption has drawn much attention recently. In case an LCD panel is driven by a low-frequency fringe field, image flickering phenomenon is detected by the naked human eye when the sign of the applied electric field is reversed. We investigated the effect of electrode spacing on the image flickering phenomenon induced by the flexoelectric effect in a fringe-field-switching (FFS) liquid crystal cell. We found that the image flicker in an FFS cell under low-frequency driving can be eliminated in a simple manner by changing the electrode spacing. GRAPHICAL ABSTRACT: